A Consensus Ochratoxin A Biosynthetic Pathway: Insights from the Genome Sequence of Aspergillus ochraceus and a Comparative Genomic Analysis - Wang, Yan; Wang, Liuqing; Wu, Fan; Liu, Fei; Wang, Qi; Zhang, Xiaoling; Selvaraj, Jonathan Nimal; Zhao, Yueju; Xing, Fuguo; Yin, Wen-Bing; Liu, Yang (Applied and environmental microbiology, 2018)
Ochratoxin A (OTA) is a significant mycotoxin that contaminates cereal products, coffee, grapes, wine, cheese, and meat. OTA is nephrotoxic, carcinogenic, teratogenic, and immunotoxic. OTA contamination is a serious threat to food safety, endangers human health, and can cause huge economic losses. At present, >20 species of the genera Aspergillus and Penicillium are known to produce OTA. Here we demonstrate that a consensus OTA biosynthetic pathway exists in all OTA-producing fungi and is encoded by a gene cluster containing four highly conserved biosynthetic genes and a bZIP transcription factor. Ochratoxin A (OTA) is a toxic secondary metabolite produced by Aspergillus and Penicillium species that widely contaminates food and feed. We sequenced and assembled the complete ∼37-Mb genome of Aspergillus ochraceus fc-1, a well-known producer of OTA. Key genes of the OTA biosynthetic pathway were identified by comparative genomic analyses with five other sequenced OTA-producing fungi: A. carbonarius , A. niger , A. steynii , A. westerdijkiae , and Penicillium nordicum . OTA production was completely inhibited in the deletion mutants (Δ otaA , Δ otaB , Δ otaC , Δ otaD , and Δ otaR1 ), and OTA biosynthesis was restored by feeding a postblock substrate to the corresponding mutant. The OTA biosynthetic pathway was unblocked in the Δ otaD mutant by the addition of heterologously expressed halogenase. OTA biosynthesis begins with a polyketide synthase (PKS), OtaA, utilizing acetyl coenzyme A (acetyl-CoA) and malonyl-CoA to synthesize 7-methylmellein, which is oxidized to OTβ by cytochrome P450 monooxygenase (OtaC). OTβ and l -β-phenylalanine are combined by a nonribosomal peptide synthetase (NRPS), OtaB, to form an amide bond to synthesize OTB. Finally, OTB is chlorinated by a halogenase (OtaD) to OTA. The otaABCD genes were expressed at low levels in the Δ otaR1 mutant. A second regulator, otaR2 , which is adjacent to the biosynthetic gene, could modulate only the expression of otaA , otaB , and otaD . Thus, we have identified a consensus OTA biosynthetic pathway that can be used to prevent and control OTA synthesis and will help us understand the variation and production of the intermediate components in the biosynthetic pathway. IMPORTANCE Ochratoxin A (OTA) is a significant mycotoxin that contaminates cereal products, coffee, grapes, wine, cheese, and meat. OTA is nephrotoxic, carcinogenic, teratogenic, and immunotoxic. OTA contamination is a serious threat to food safety, endangers human health, and can cause huge economic losses. At present, >20 species of the genera Aspergillus and Penicillium are known to produce OTA. Here we demonstrate that a consensus OTA biosynthetic pathway exists in all OTA-producing fungi and is encoded by a gene cluster containing four highly conserved biosynthetic genes and a bZIP transcription factor.